Cyclic Voltammetry as an Electroanalytical Tool for Analysing the Reaction Mechanisms of Copper in Chloride Solution Containing Different Azole Compounds - Finšgar, Matjaž; Xhanari, Klodian; Ćurković, Helena O. (Current Analytical Chemistry, 2020)
Background: Cyclic voltammetry is widely employed in electroanalytical studies because it provides fast information about the redox potentials of the electroactive species and the influence of the medium on the redox processes. Azole compounds have been found to be effective corrosion inhibitors for copper in chloride-containing solutions. The aim of this work was to investigate in detail the influence of the addition of various azole compounds on the oxidation mechanism of copper in chloride-containing solutions, using cyclic voltammetry. Methods: The influence of thirteen azole compounds, at three different concentrations on the electrochemical/ chemical reactions of pure copper immersed in 3 wt.% NaCl solution was studied using cyclic voltammetry at different scan rates. The change of the peak current and potential with the scan rate were investigated. The possible linearity was compared with the theoretically derived mechanism. The possible reaction mechanisms were discussed based on the linearity of these parameters (peak current and potential) with the scan rate compared to theoretically derived models. Results: Both the peak current and peak potential of the copper samples immersed in chloridecontaining solutions with additions of the majority of azole compounds showed linearity with the square root of the scan rate, suggesting that copper follows the Müller-Calandra passivation model. The same behavior was also found for copper in chloride-containing solutions without additions of azole compounds. A linear variation of the peak potential with the natural logarithm of the scan rate and linear variation of the peak potential with the square root of the scan rate was observed for the copper samples immersed in chloride-containing solutions with the addition of 10 mM of 2-mercapto-1- methylimidazole, imidazole, or 2-aminobenzimidazole. This suggests that copper follows irreversible redox reactions under a diffusion controlled process. No other linear relations of the peak current and peak potential with the scan rate were found. Conclusion: Copper oxidation in chloride-containing solutions is controlled by passivation (following the Müller-Calandra passivation model) upon the addition of the majority of the selected azoles. In the minority of cases, irreversible redox reactions that follow a diffusion-controlled process were identified. None of the systems followed an adsorption-controlled process. Moreover, none of the tested systems underwent reversible redox reactions that followed a diffusion controlled process.
Keywords: reaction mechanisms